Minimizing the Number of Dropouts in University Pedagogy Online Courses - Samuli Laato; Emilia Lipponen; Heidi Salmento; Henna Vilppu; Mari Murtonen (Portugal, 2022)
Students’ engagement and retention in online courses have been found to be in general significantly lower than in contact teaching. Multiple reasons for this exist, but improving student retention is ubiquitously seen as a beneficial improvement. We take a look at student engagement in online courses aimed specifically for university teachers and doctoral students, and use a mixed methods approach to obtain a holistic understanding of student engagement in our domain. We analyse quantitative data from two cases (n=346 and n=271) collected from students of three university pedagogy online modules over the course of years 2016-2017. We identify key moments in our modules where students drop out and, for example, differences in dropout rates between various demographics (i.e. faculty and whether the student is a university staff member or not). The main moment where students drop out is found to be in the very beginning of the courses, and the introduction of a pre- and post-tes t to the courses improved retention. This study suggests that when all other factors affecting student engagement are in order, additional focus should be paid to the very beginning of the course and get as many students to do the first couple tasks as possible in order to reduce the dropout rate.
Proceedings of the 11th International Conference on Computer Supported Education - Volume1: (CSEDU 2019)